Kesiapan Guru IPA SMP Negeri 3 Langsa Terhadap Pelaksanaan Kurikulum 2013 Tahun Ajaran 2018/2019 - Deby Sintiya; Nurmasyitah Nurmasyitah; Teuku Junaidi (Jurnal Pendidikan Fisika dan Sains, 2019)
Curriculum change is done not without a clear reason, because the curriculum is structured in order to meet the growing demands in society. With changes in community life that continues to evolve, the curriculum used must be adjusted so that education can keep pace with the changing times and the development of science and technology. Assessment standards that have been imposed by the Ministry of Education and Culture (Kemendikbud). This type of research is a qualitative descriptive study. The research population was all 79 junior high school teachers in Langsa, a sample of the data source was carried out in a porposive manner, in this study the sample taken only involved natural science teachers, amounting to 8 teachers. Data collection using questionnaires and interviews. Data analysis techniques using descriptive analysis. The results of the descriptive analysis of each aspect are 1) The principles of valuation are (90%), 2) The form of valuation is (100%), 3) The evaluation mechanism is (93%), 4).The evaluation procedure is (86%). Based on the results of all aspects of teacher readiness in carrying out the assessment process of the revised 2013 curriculum is (92.25%). Keywords: Curriculum, Teacher Readiness and Assessment Standards